2020
DOI: 10.1039/d0qm00500b
|View full text |Cite
|
Sign up to set email alerts
|

Band gap engineering of donor–acceptor co-crystals by complementary two-point hydrogen bonding

Abstract: We report a detailed investigation of a series of new charge-transfer (CT) complexes assembled via a two-point complementary hydrogen bonding (H-bonding) of diindolopyrrole (DIP) electron donors with o-quinone and diazafluorenone...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 59 publications
1
14
1
Order By: Relevance
“…The close contact between donor and acceptors brought about by hydrogen bonding allowed for electron transport between them. These observations led to a series of recent publications which expanded the structural scope of both donor and acceptor moieties 55–57 . As a result of complexation between donor and acceptor small molecules, the authors observed lower band gaps, intense absorption in the near infrared region, and short inter‐chromophore separation, all of which make these molecules interesting candidates for organic transistors.…”
Section: Hydrogen Bondingmentioning
confidence: 99%
“…The close contact between donor and acceptors brought about by hydrogen bonding allowed for electron transport between them. These observations led to a series of recent publications which expanded the structural scope of both donor and acceptor moieties 55–57 . As a result of complexation between donor and acceptor small molecules, the authors observed lower band gaps, intense absorption in the near infrared region, and short inter‐chromophore separation, all of which make these molecules interesting candidates for organic transistors.…”
Section: Hydrogen Bondingmentioning
confidence: 99%
“…This shift depends on the nature of the metal coordinated to the organic ligand and can reach up to 1.7 V. Thus, the interaction of Lewis acid with the electron acceptor can promote redox transformations, including catalysis. Besides, the ability to control the position and nature of the frontier orbitals of organic electron acceptors can serve as a convenient tool for fine-tuning photoactive donor−acceptor systems 66 for photovoltaics, nonlinear optics, and electrochromic compounds and sensors.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…22−25 For example, a singlepoint H-bonding was used to control the assembly of a TTFimidazole donor with various acceptors, where the H-bonding polarization strengthens the CT interactions, leading to a near-IR (NIR) absorption and, often, metallic conductivity in complexes with a large ΔE offset (up to 0.7 eV). 22,23 Recently, our lab reported that complementary two- 26,27 and threepoint 28−30 H-bonding can be used for a reliable coassembly of various π-electron donors and acceptors with a relatively high ΔE offset (0.8−2.5 eV). In the case of unidirectional (two-point) H-bonding we observed a strong enhancement of the D−A interactions due to H-bonding.…”
mentioning
confidence: 99%
“…In the case of unidirectional (two-point) H-bonding we observed a strong enhancement of the D−A interactions due to H-bonding. 26,27 However, not having X-ray crystallographic data for corresponding D/A cocrystals without H-bonding, the understanding of the effect of H-bond polarization on the CT interactions relied on the density functional theory (DFT) predictions and solution studies.…”
mentioning
confidence: 99%